Nonunion of ulnar diaphysis after Monteggia fracture of a right forearm in a 55-year-old patient - Are all methods effective? Case report - Bąk, Marcin; Potoczniak, Bartosz; Dziedzic, Artur; Kozak, Łukasz; Blicharski, Tomasz; Dziedzic, Urszula; Massalska-Małecka, Teresa; Jarecki, Jaromir (Journal of Education, Health and Sport, 2019)
Fractures of the forearm make up about 10-14% of all fractures. Monteggia lesions account for 1-6% of the forearm fractures. The eponym “Monteggia fracture” is a term used for fracture of ulnar proximal shaft with concomitant dislocation of the radial head in the proximal radioulnar joint [1]. Its clinical symptoms are: pain, edema, local sensitivity, friction between bone fragments, deformation of the limb, loss of function in elbow joint and the forearm. Radiographs in AP and lateral views of the entire forearm, with wrist and elbow joint, are mandatory for successful diagnosis [2]. There are four types of fractures in the Bado classification system of the Monteggia lesion [3]. All Monteggia fractures in adults require surgical procedure of open reduction and internal fixation as a method of choice [4]. Delayed bone adhesion, nonunion, synostosis, instability of the radial head, nerve damage and restriction of movement are main complications of surgical intervention. We present a case of a 55-year-old patient with Monteggia fracture of a right forearm with a complication of a nonunion of the ulnar shaft, despite undergoing surgical procedure of open reduction and internal fixation. We describe consecutive methods of treatment that resulted in complete bone adhesion. Nonunion typically occurs due to technical mistakes in initial surgical intervention. Application of the correct reparative technique with autogenous bone graft and compression plates allows to fully heal nonunion of the bone.